2018
DOI: 10.1155/2018/9021371
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity, Antioxidant, and Antifatigue Activities of Protein‐Rich Extract from Oviductus ranae

Abstract: The paper investigated the preparation, amino acid composition, acute toxicity, and in vitro and in vivo antioxidant, coupled with in vivo antifatigue activities of protein-rich extract of Oviductus ranae (PEOR). The results indicated that PEOR possesses high-safety property with maximum tolerated dose (MTD) higher than 20 g/kg in mice, shows weak scavenging capacities against hydroxyl, superoxide anion, and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals, as well as ferric-reducing antioxidant power in vitro, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…It is worthwhile to note that bioactive studies and clinical practices provide strong evidence for the functions of OR on immunomodulation, antioxidation, and antifatigue. In previous work, we also observed that protein-rich extracts from OR elicit significant antioxidant and antifatigue activities [84].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is worthwhile to note that bioactive studies and clinical practices provide strong evidence for the functions of OR on immunomodulation, antioxidation, and antifatigue. In previous work, we also observed that protein-rich extracts from OR elicit significant antioxidant and antifatigue activities [84].…”
Section: Discussionmentioning
confidence: 91%
“…In a previous work [84], we investigated the preparation, amino acid composition, and in vitro and in vivo antioxidant activities of WPOR and found that WPOR exert weaker in vitro radical-scavenging capacities to hydroxyl, superoxide anion, and DPPH as well as ferric-reducing power compared with vitamin C (VC) but show stronger antioxidant effects in an ethanol-induced oxidative stress mouse model. These results were in accordance with the general findings that proteins and polypeptides usually exhibit lower in vitro free radical-scavenging capacities than their smaller peptides and amino acids, due to the fact that substances with smaller molecular weight may be prone to interact with free radicals more effectively [131].…”
Section: Biological Functions Of Oviductus Ranaementioning
confidence: 99%
See 1 more Smart Citation
“…VC was used as positive control. The hydroxyl radical-scavenging rate was calculated according to the following equation (Zhang et al, 2018):…”
Section: Hydroxyl Radical-scavenging Activitymentioning
confidence: 99%
“…Recent studies have found that OR shows immune enhancement, anti-fatigue, antiosteoporosis, anti-oxidation, anti-apoptosis, reproductive protection and estrogen-like effects. The proteins and steroids of OR have been well studied (Wang et al, 2010;Zhang et al, 2018). However, little information is available on the Polysaccharides from OR (POR).…”
Section: Introductionmentioning
confidence: 99%